Effects of the Maillard Reaction on the Structural and Functional Properties of Camel Whey Protein - Ying Liu; Chunyan Ran; Hongyi Zhang; Yaqi Cheng; Minaer Huanbieke; Yuying Liu; Jie Yang; Yuqing Mei; Yang Qu (Foods)
Consumer demand for dairy products like cheese and curds has resulted in a rise in whey production, which has caused significant waste and environmental issues. For this reason, improving the functional characteristics of whey proteins and their usage value are essential. In this study, camel whey protein–galactose conjugates (CWP-Gal) and camel whey protein–glucose conjugates (CWP-Glu) were prepared through the Maillard reaction, and their structural and functional properties were characterized. Improvements in solubility of 14.90% and 8.17%, emulsification activity of 15.53% and 13.64%, and foaming capacity of 113.95% and 106.03% were demonstrated by CWP-Gal and CWP-Glu in comparison to camel whey protein (CWP). Circular dichroism analysis revealed secondary structure alterations in CWP-Gal and CWP-Glu compared to CWP. SDS-PAGE, FT-IR, and intrinsic fluorescence spectroscopy all verified that sugar molecules and proteins were covalently conjugated. SEM analysis revealed that the conjugates had a more sparsely packed microstructure. The results demonstrate that CWP-Gal exhibits enhanced structural stability and superior functional properties, providing a scientific basis for its potential utilization in the food industry.